2000
DOI: 10.1161/01.atv.20.1.210
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino Acid Deletion in the Carboxy Terminal of Apolipoprotein A-I Impairs Lipid Binding and Cellular Interaction

Abstract: Abstract-The carboxy-terminal region of apolipoprotein (apo) A-I has been shown by mutagenesis or synthetic peptides to play an important role in lipid binding. However, the precise functional domain of the C-terminal remains to be defined. In this study, apoA-I Nichinan, a naturally occurring human apoA-I variant with a deletion of glutamic acid 235, was expressed in Escherichia coli to examine the effect of this mutation on the functional domain of apoA-I for lipid binding and related consequences. A dimyris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…It was reported previously that recombinant proapoA-I Nichinan solubilizes DMPC vesicles more slowly than normal proapoA-I. 5) Our present results suggest that the reduced rate of microsolubilization observed in proapoA-I Nichinan is caused by direct influences of the impaired lipid interaction of the C-terminal region. Hydrophobic acyl chains of phospholipid molecules at the edge of discoidal particles are covered with amphipathic a-helices of apoA-I to stabilize the discoidal HDL structure.…”
Section: )supporting
confidence: 69%
See 1 more Smart Citation
“…It was reported previously that recombinant proapoA-I Nichinan solubilizes DMPC vesicles more slowly than normal proapoA-I. 5) Our present results suggest that the reduced rate of microsolubilization observed in proapoA-I Nichinan is caused by direct influences of the impaired lipid interaction of the C-terminal region. Hydrophobic acyl chains of phospholipid molecules at the edge of discoidal particles are covered with amphipathic a-helices of apoA-I to stabilize the discoidal HDL structure.…”
Section: )supporting
confidence: 69%
“…4,5) Computational analysis of the amino acid sequence of human apoA-I reveals that residues 44-243, encoded by exon 4, is composed of 11-or 22-amino acid tandem repeats, which can form amphipathic a-helices mostly punctuated by proline residues. 6) Studies of synthetic peptides corresponding to each of 22-residue amphipathic segments of apoA-I have shown that the last repeated helix (residues 220-241) has greatest lipid affinity.…”
mentioning
confidence: 99%
“…The importance of the C terminus (aa 187-243) of apoA-I in both phospholipid binding and cholesterol efflux has been shown previously (41)(42)(43), suggesting these two properties may be related. To determine if either the N-terminal globular domain or helix 1 are involved in cellular cholesterol efflux, we compared the efflux from cholesterol-loaded J774 macrophages to lipid-free His-Wt, His-⌬1-43, His-⌬1-65, and His-⌬210 -243 apoA-I (Table I).…”
Section: The N Terminus Of Apoa-i Is Essential For Hdl Maturationmentioning
confidence: 78%
“…The first pathway appears to be mediated by the ATP binding cassette transporter (ABCA1) (37), and the second may involve the scavenger receptor class B, type I (SR-B1) (38). The role of distinct apoA-I domains in cellular cholesterol efflux mediated by either lipid-free or lipidated apoA-I has been addressed by using monoclonal antibodies against epitopes distributed along the entire apoA-I sequence, and by using natural or recombinant apoA-I mutants (39)(40)(41)(42)(43)(44)(45)(46). Taken together, earlier results suggest that sequences in the central (39)(40)(41)(42) and C-terminal (43,44,47) regions of apoA-I may facilitate cholesterol efflux to lipidated apoA-I by interacting with specific lipid domains, or proteins in the cell membrane.…”
Section: Downloaded Frommentioning
confidence: 99%